Oxidative Stress in the Pathogenesis of Antiphospholipid Syndrome: Implications for the Atherothrombotic Process - Cristina Nocella (MDPI AG, 2021)
Atherothrombosis is a frequent complication of the clinical history of patients with antiphospholipid syndrome (APS). Both atherothrombosis and APS are characterized by increased oxidative stress. Oxidative modifications are implicated in the formation of antiphospholipid antibodies, which in turn may favour the oxidative imbalance by increasing the production of reactive oxidant species (ROS) or by a direct interaction with pro-oxidant/antioxidant enzymes. As a result of these processes, APS patients suffer from an oxidative imbalance that may contribute to the progression of the atherosclerotic process and to the onset of ischemic thrombotic complications. The aim of this review is to describe mechanisms implicated in the formation of ROS in APS patients and their involvement in the atherothrombotic process. We also provide an overview of potential therapeutic approaches to blunt oxidative stress and to prevent atherothrombotic complications in these patients.